Production of English vowel duration by multilingual speakers of Namibian English - Haapanen, Katja; Saloranta, Antti; Peltola, Kimmo U.; Tamminen, Henna; Uwu-khaeb, Lannie; Peltola, Maija S. (Cambridge University Press, 2025)
The aim of this study was to examine spoken Namibian English by investigating how multilingual Namibian speakers produce vowel durations in pre-lenis and pre-fortis positions, and how those vowel durations compare to British English vowel durations in the same words. In British English and most other English varieties, vowel duration is affected by the voicing of the following consonant, so that vowels preceding phonologically voiced consonants are longer (pre-lenis lengthening) and vowels preceding phonologically voiceless consonants are shorter (pre-fortis clipping). The production data was collected using orthographic stimuli that were monosyllabic English words with voiced and voiceless final consonants after the target vowels. The data were collected from 14 multilingual Namibian English speakers. The vowel durations produced by the speakers in pre-lenis and pre-fortis position were first compared to each other and then to those produced by nine British English speakers in an earlier study. The results showed that the pre-lenis vowels were clearly longer than the pre-fortis vowels, and there were no differences between Namibian and British English vowel durations in most of the tested words. The results offer new insights into the realization of vowel duration in pre-lenis and pre-fortis positions in Namibian English.